Inter- and intra- observer reliability of the offera method for assessing exposure risk of computer work-related to wmsds. (January 2019) - Rahman, M N A; Mohamad, S S; Marwah, O M F; Masood, I; Hassan, M F; Arifin, A M T; Haq, R H A; Ahmad, S; Haw, H F; Abdullah, H
Abstract: The purpose of this study was to evaluate inter- and intra- observer reliability of the observers assessing office workers performing their jobs using the Office Ergonomic Risk Assessment (OFFERA) method. 44 Industrial Engineering students at UTHM participated in a training session on inter- and intra- observer reliability. The period interval between inter- and intra- observer training session was 1 week. Three different jobs were assessed by observer using the OFFERA method. Through the three different tasks, the average of inter- and intra- observer reliability ranged between good to very good agreement. Meanwhile, the level of agreement for the intra- observer (K = 0.68-0.96) was higher than the inter-observer (K = 0.62-0.94). Items with the strongest agreement (K = 0.96) were related to armrest, document holder and keyboard wrist rest. The OFFERA method has both good and very good agreement in terms of reliability. The observers stated that it was easy to evaluate the ergonomic risk at office using this simple tool.